Development and Validation of a 28-gene Hypoxia-related Prognostic Signature for Localized Prostate Cancer - Yang, Lingjian; Roberts, Darren; Takhar, Mandeep; Erho, Nicholas; Bibby, Becky A.S.; Thiruthaneeswaran, Niluja; Bhandari, Vinayak; Cheng, Wei-Chen; Haider, Syed; McCorry, Amy M.B.; McArt, Darragh; Jain, Suneil; et al. (EBioMedicine, 2018)
Hypoxia is associated with a poor prognosis in prostate cancer. This work aimed to derive and validate a hypoxia-related mRNA signature for localized prostate cancer. Hypoxia genes were identified in vitro via RNA-sequencing and combined with in vivo gene co-expression analysis to generate a signature. The signature was independently validated in eleven prostate cancer cohorts and a bladder cancer phase III randomized trial of radiotherapy alone or with carbogen and nicotinamide (CON). A 28-gene signature was derived. Patients with high signature scores had poorer biochemical recurrence free survivals in six of eight independent cohorts of prostatectomy-treated patients (Log rank test P < .05), with borderline significances achieved in the other two (P < .1). The signature also predicted biochemical recurrence in patients receiving post-prostatectomy radiotherapy (n = 130, P = .007) or definitive radiotherapy alone (n = 248, P = .035). Lastly, the signature predicted metastasis events in a pooled cohort (n = 631, P = .002). Prognostic significance remained after adjusting for clinic-pathological factors and commercially available prognostic signatures. The signature predicted benefit from hypoxia-modifying therapy in bladder cancer patients (intervention-by-signature interaction test P = .0026), where carbogen and nicotinamide was associated with improved survival only in hypoxic tumours. A 28-gene hypoxia signature has strong and independent prognostic value for prostate cancer patients. •We identified genes regulated by hypoxia in prostate cancer cell lines.•In a cohort of primary tumours, the hypoxia regulated genes were reduced to a prognostic signature.•The mRNA abundance signature was prognostic of biochemical recurrence/metastatic recurrence in 11 independent cohorts. Hypoxia, i.e. insufficient supply of oxygen, is an important micro-environmental factor in solid tumours, including prostate cancer. In this work, we identified genes whose abundance were affected by induced hypoxia (1% oxygen concentration) from prostate cancer cell lines. The hypoxia-regulated genes were then refined into a signature, i.e. a biomarker consisting of multiple genes, based on their ability to predict patient outcome after radical prostatectomy. The gene signature predicted the risk of developing biochemical and metastatic recurrence in >1000 patients with primary tumours receiving varying treatments. The prognostic value was independent from existing clinic-pathological factors.